181k views
0 votes
Simplify the expression

Simplify the expression-example-1

2 Answers

4 votes
√18x^4y^3
= 3x^2y√(2y)

hope it helps
User Saikou
by
6.8k points
5 votes
Answer:

3 √(2) x^2 y^(3/2)
This can be rewritten as:

3x^2 √(2y^3)

Step-by-step explanation:
Before we begin, remember the following:
√ab = √a * √b
√xᵃ = x^(a/2)

Now, for the given, we have:

√(18x^4y^3)

18 can be rewritten as 9 * 2
Therefore, the given expression would now become:

√(9*2x^4y^3)

Distributing the root as mentioned in the above rules, we would get:

√(9) * √(2) * √(x^4) * √(y^3)

We know that:

√(9) = 3 (we would disregard the negative value of the root)

√(x^4) = x^(4/2) = x^2

√(y^3) = y^(3/2)

Substitute with the above in the expression, we would get the final answer:

3 √(2) x^2 y^(3/2)
This can be rewritten as:

3x^2 √(2y^3)

Hope this helps :)
User Burton Samograd
by
5.9k points